Inhibition of 6-phosphogluconate Dehydrogenase Reverses Cisplatin Resistance in Ovarian and Lung Cancer - Zheng, Wujian; Feng, Qi; Liu, Jiao; Guo, Yanke; Gao, Lvfen; Li, Ruiman; Xu, Meng; Yan, Guizhen; Yin, Zhinan; Zhang, Shuai; Liu, Shuangping; Shan, Changliang (Frontiers in Pharmacology, 2017)
Cisplatin (DDP) is currently one of the most commonly used chemotherapeutic drugs for treating ovarian and lung cancer. However, resistance to cisplatin is common and it often leads to therapy failure. In addition, the precise mechanism of cisplatin resistance is still in its infancy. In this study, we demonstrated that the oxidative pentose phosphate pathway (PPP) enzyme 6-phosphogluconate dehydrogenase (6PGD) promotes cisplatin resistance. We showed that cisplatin-resistant cancer cells (C13* and A549DDP), had higher levels of 6PGD compared to their cisplatin-sensitive counterparts (OV2008 and A549). Furthermore, ovarian and lung cancer patients with higher 6PGD levels have worse survival outcomes relative to patients with lower 6PGD expression. Interestingly, we found that the upregulation of 6PGD in cisplatin-resistant cells was due to the decreased expression of miR-206 and miR-613, which we found to target this enzyme. We further demonstrate that suppressing 6PGD using shRNA, inhibitor or miR-206/miR-613, either as single agents or in combination, could sensitize cisplatin-resistant cancer cells to cisplatin treatment and thereby improving the therapeutic efficacy of cisplatin. Taken together, our results suggest that 6PGD serves as a novel potential target to overcome cisplatin resistance.